Viscous dissipation and Joule heating effects on steady MHD combined heat and mass transfer flow through a porous medium in a rotating system - Alam, Mahmud Md; Hossain, M. Delower; Hossain, M Arif (Journal of Naval Architecture and Marine Engineering, 2011)
<!–[if gte mso 9]> Normal 0 MicrosoftInternetExplorer4 <![endif]–> <!–[endif] –>Viscous dissipation and Joule heating effects on steady MHD combined heat and mass transfer flow through a porous medium along a semi-infinite vertical porous plate in a rotating system has been studied numerically. The boundary layer equations have been transformed into dimensionless coupled nonlinear ordinary differential equations by appropriate transformations. The similarity solutions of the transformed dimensionless equations for the flow field and heat and mass transfer characteristics are obtained by shooting iteration technique. Numerical results are presented in the form of primary and secondary velocities, temperature and concentration distributions within the boundary layer for different parameters entering into the analysis. Finally, the effects of the pertinent parameters on the Skin-friction coefficients, Nusselt number and Sherwood number are also examined. Keywords: MHD; Joule heating; porous medium; rotating system simulation. doi: http://dx.doi.org/10.3329/jname.v8i2.5055 Journal of Naval Architecture and Marine Engineering 8(2011) 105-120